Turismo Comunitario, Alternativa De Desarrollo Turístico Estudio De Caso: Producto Turístico Para La Comunidad Paquiestancia, Parroquia San José De Ayora, Cantón Cayambe, Provincia De Pichincha - Ecuador - Chávez Velásquez, Carlos Renato; Carrasco Baquero, Juan Carlos; Aguirre Merino, Christiam; Novoa Guaján, Polo Wilfrido (European Scientific Journal, ESJ, 2016)
Ecuador has a variety of attractions that highlight the scenic beauty and diversity of flora and fauna, the warmth of its people and its cultural heritage has made of Ecuador a tourist destination that is worth to visiting and admiring. It is a tourist destination in constant growth that generates the need to create new tourism products, so community tourism is an option of tourism that integrate communities with visitors from an intercultural perspective, ensuring the proper use of tourist resources. This research proposes to carry out in a first stage the design of a community tourism product in the province of Pichincha, Paquiestancia community, through the inventory of natural and cultural attractions using the methodology of MINTUR 2004 and the INPC; 2011. Followed by the market study, analyzing the demand and supply in the sector, applying surveys after defining the sample for national and international tourists, in which was obtained the tastes and preferences of visitors, which allows designing tour packages according to their requirements. Finally for the operation of this product, were designed four packages, which intended to encourage and maintain traditions to the community, generating social, economic and environmental benefits for sustainable development.